Bolsonarismo e fascismo clássico: aproximações, distanciamentos e caracterização - Resende, Lucas Eduardo Prais de Castro (2024)
This work, through a process of comparison with classical Italian fascism, examined one of the most relevant Brazilian political, social and cultural phenomena of the 21st century: bolsonarism. This effort took place through a bibliographical discussion, and unfolded on an analysis that aimed to find points of similarity and difference between the two political movements, in order to develop a pertinent characterization of the recent brazilian phenomenon. Supported by this process of analogy, this writings was dedicated to investigating in which aspects the movement led by former president Jair Messias Bolsonaro approaches Benito Mussolini's regime, and in which aspects it distances itself, giving particular emphasis to the relationship between these two phenomena and unionism. The question we aimed to answer is whether it is appropriate to classify Bolsonarism as a fascist ideology and movement. After dedicated analysis, it was concluded that it is appropriate, given its similarities with classic fascism, however, contextualizing the movement historically, to name Bolsonarism as a neofascist phenomenon.